2017
DOI: 10.1007/s12649-017-9916-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Addition of Biochar and Coffee Grounds on the Biological Properties and Ecotoxicity of Composts

Abstract: coffee grounds and yeast effluent. The inhibitory effect on the germination capacity was alleviated in treatments with biochar. The addition of biochar to compost with sewage sludge decreased the abundance of Escherichia coli and Salmonella ssp. and increased the total number of bacteria and fungi. In the case of composts with coffee grounds, biochar had an opposite effect to that observed for composts with sewage sludge. Conclusions Biochar to sewage sludge and coffee grounds reduced ecotoxicity of composts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…The addition of biochar to compost with sewage sludge decreased the abundance of indicative microorganisms E. coli and Salmonella ssp. and increased the total number of bacteria and fungi [41]. The physico-chemical characteristics of biochar and zeolite may explain the observed changes in the bacterial and fungal communities.…”
Section: Discussionmentioning
confidence: 89%
“…The addition of biochar to compost with sewage sludge decreased the abundance of indicative microorganisms E. coli and Salmonella ssp. and increased the total number of bacteria and fungi [41]. The physico-chemical characteristics of biochar and zeolite may explain the observed changes in the bacterial and fungal communities.…”
Section: Discussionmentioning
confidence: 89%
“…All these parameters were determined in triplicate to ensure the preciseness of the measurements. [28]. Moreover, to ensure the high quality of the end product, heavy metals content was measured in an external lab, to be then compared to the German quality requirements for compost, as used in gardening and agriculture.…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Based on the AT 4 value it can be stated that the 12 weeks of maturation reduced the value of the AT 4 parameter to a level that results in the sufficient stabilization of the material [10,40]. Some authors have found that the AT 4 value can be much higher for SSC than for composts from other wastes [12,25]. In a current study an interesting effect was a high level (44.6 Nl kg −1 DM) of GS 21 for the sample after 2 weeks of maturation (No.…”
Section: Stability Degree Tests and Gas Production Potentialmentioning
confidence: 99%
“…Stabilized waste should be characterized by a low value of the AT 4 parameter, below 10 mg O 2 g −1 DM [10]. Many tests are used to assess the stability of waste compost [10,12,[25][26][27][28]. In recent years, a number of automated respirometers have become available on the market, each with a proven 1 3 capability to measure O 2 consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation